Learning Tahfidz Al-Qur'an During the Covid-19 Pandemic - Susanto, Susanto; Desrani, Ayu; Zamani, Dzaki Aflah (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
This research discussed the learning of tahfidz Al-Qur’an by applying online and offline learning at two different schools. The selection of learning methods and learning systems is one that is very influential in memorizing the Qur'an for students. To get the discussion material from this research, the researcher conducted a series of data searches through interviews, documentation, and observations at schools. After the data was collected, the researcher conducted a critical analysis using in-depth data triangulation techniques. The findings of this study indicate that there is a very significant difference in the implementation of learning between the two institutions. Junior High School Plus Babussalam carries out online learning using the classical method, namely the teacher sends voice notes via WhatsApp and students follow it and also collects memorization using WhatsApp and the evaluation is done face-to-face. While the Tahfidz Yatim Dhuafa Islamic Boarding School continues to do offline learning using the Pakistani method, namely by depositing new memorization to the teacher along with old memorization. This method is effective to use, but it is quite hard because students are required to repeat and add memorization simultaneously.